Antioxidant Properties of Mesembryanthemum crystallinum and Carpobrotus edulis Extracts - Bouftira, I.; Abdelly, C.; Sfar, S. (Asian Journal of Chemistry, 2010)
Extraction efficiency using different solvents on antioxidant capacities of Mesembryanthemum crystallinum and Carpobrotus edulis was measured. The dried extracts were screened for their radical scavenging activity using a,a-diphenyl- b-picrylhydrazyl (DPPH) method. The order of antioxidant capacity of M. crystallinum in different solvents was found to be petroleum ether > ethyl acetate > chloroform > methanol > flavonoids and water. The order of antioxidant capacity of C. edulis was found to be flavonoids > methanol > chloroform > water and petroleum ether. Petroleum ether and flavonoids extracts from M. crystallinum and C. edulis showed highest antioxidant activity at 500 μg/mL. Results of the present study may be due to the extent of antioxidant capacity of each extract is in accordance with the amount of chrolophylls, carotenoids, phenolics and others different antioxidant compounds that can be presents in the extracts.